Intramolecular carboxylic group-assisted cleavage of N-(2-hydroxyphenyl)-phthalamic acid (7) and N-(2-methoxyphenyl)-phthalamic acid (8): Absence of intramolecular general acid catalysis due to 2-OH in 7 - Ariffin, Azhar; Khan, M.N.; Sim, Y.L. (2006)
The values of pseudo first-order rate constants (k(obs)) for the cleavage of N-(2-hydroxyphenyl)phthalamic acid (7), obtained at 4.9 x 10(-2) M HCl, 35 degrees C, and within CH(3)CN content range 2-80% (v/v) in mixed aqueous solvent are smaller than k(obs) for the cleavage of N-(2-methoxyphenyl)phthalamic acid (8), obtained under almost similar experimental conditions, by nearly 1.5- to 2-fold. These observations show the absence of expected intramolecular general acid catalysis due to 2-OH group in 7. The values of k(obs) for the cleavage of 7 and 8 decrease by more than 20-fold with the increase in the content of CH(3)CN from 2 to 80-82% (v/v) in mixed aqueous solvent. The kinetic data reveal that in acidic aqueous cleavage of 7, N-cyclization (leading to the formation of imide) and O-cyclization (leading to the formation of phthalic anhydride) vary from similar to 10 to 15% and similar to 90 to 85%, respectively, with the increase in CH3CN content from 2 to 80% (v/v). Similar increase in CH3CN content causes increase in N-cyclization from similar to 0 to 5% and decrease in O-cyclization from similar to 100 to 95% in the acidic aqueous cleavage of 8. Some speculative, yet conceivable, reasons for nearly 10 and 0% N-cyclization in the cleavage of respective 7 and 8 at low content of CH3CN have been described. (c) 2006 Wiley Periodicals, Inc.